Removal of Methyl Red using Chemical Impregnated Activated Carbon Prepared from Parkia speciosa Pod (Petai) as a Potential Adsorbent (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Textile industry is one of the major contributors either in terms of employment or economies. This industry has provided variety of daily necessity such as sources of yarn and clothing. Extensively use of dyes in this textile industry has created water pollution. The serious problem happened when the daily water usage is from the untreated effluents which are discharged directly into water bodies. However, the disposed dyes into environment can be treated with adsorbents such as activated carbon via adsorption process. In this study, Parkia speciosa (petai) pods were chosen as the raw material from agricultural waste to produce activated carbon. Activated carbon was prepared from two different chemicals and application of four different carbonization time. Two parameters studied in the experiment are initial dye concentration and contact time. From the result, 100% of methyl red was removed by the activated carbon impregnated with zinc chloride solution at 1 hour carbonization time. The optimum time and initial concentration of dye was 30 minutes and 10 ppm respectively with the percentage removal of 100%. Thus, this result could contribute some knowledge on the use of alternative adsorbent from agricultural waste impregnation with specified chemicals in treating textile industrial wastewater.
Keywords: methyl red dye; adsorption; Parkia speciosa; activated carbon